PROCESS OPTIMIZATION AND KINETICS OF BIOLUBRICANT SYNTHESIS FROM FLUTED PUMPKIN SEED - Matthew Menkiti; Humphrey Anaehobi; Kechinyere Oyoh; Patrick Nnaji (European Scientific Journal, ESJ, 2015)
Fluted pumpkin biolubricant (FPBL) was synthesized by transesterification of fluted pumpkin methyl ester (FPME) and trimethylolpropane (TMP) using calcium hydroxide, Ca(OH)2 catalyst. First and second order kinetic models were analyzed to choose the optimum one regarding their relative simplicity and accuracy of fitting the experimental data obtained at different operating conditions. The second order kinetic model gave the best fit to the experimental data with an overall rate constant of 2.05 × 10−1 (%wt/wt min ◦C)−1 and a regression value of 0.958. The kinetic energy for the synthesis of FPBL was estimated to be 40.65 kJ/mol. Response Surface Methodology (RSM) via Central Composite Design (CCD) was used to carry out the optimization of the transesterification process. The optimum conditions for the yield of TMP triester were 160°C, 6 h reaction time and a mole ratio (MME:TMP) of 6:1 at which the triester yield was 81.42%. The properties of FPBL met the requirement for ISO VG32 and VG46 viscosity grades, and were found comparable to other plant based biolubricants such as palm oil and calophyllum oil biolubricants.